Pain treatment in patients with acute pancreatitis: A randomized controlled trial - Gülen, Bedia; Dur, Ali; Serinken, Mustafa; Karcıoğlu, Özgür; Sönmez, Ertan (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: In this study, the analgesic effectiveness of tramadol, a synthetic opioid, was compared with paracetamol and dexketoprofen in adult patients with acute pancreatitis in the emergency department. Materials and Methods: Study drugs were similar in color and appearance, enabling the patients to be blind to the intervention. Study patients were intravenously administered 1 g paracetamol, 50 mg dexketoprofen trometamol, or 1 mg/kg tramadol with 100 mL normal saline with a 4-5 min infusion. Pain measurements of the patients were conducted at baseline and 30 min after the treatment intervention. Changes in pain scores were calculated by subtracting the median scores at baseline and 30 min as pairs. Results: In this study, 90 patients were enrolled and included in the final analysis. The study subjects had a mean age of 53.5±13.3 years and 58.9% (n=53) of them were male. Gallstones and biliary etiology for pancreatitis was documented in 73.3% (n=66) of patients. Mean VAS scores at baseline and 30 min were similar in the three groups. Similarly, the change of scores from the baseline to the 30th minute did not differ among the groups. Comparison of pain improvements failed to reveal any differences among groups. Conclusion: Intravenous paracetamol, dexketoprofen, and tramadol are not superior to each other in the management of pain caused by nontraumatic acute pancreatitis.